Re-examining the Relationship between Income Inequality and Corruption by Using Index of Public Integrity - Sadaf Basharat (NUST Journal of Social Sciences and Humanities, 2021)
Against the backdrop of recent global events which have highlighted the political salience of rising income inequality and corruption, this paper has sought to re-examine the relationship between income inequality and corruption by employing an objective measure for control of corruption, the recently developed Index of Public Integrity (IPI) that constitutes a marked departure from previous research which has used subjective measures for corruption. The cross-country analysis indicates that a strong negative correlation exists between income inequality and control of corruption measured by Gini coefficient and IPI respectively, which means that increased income inequality is associated with increased level of corruption. The strength of the relationship remains strong with the inclusion of controls for level of democratisation and economic development.